2021
DOI: 10.3390/jpm11030160
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use Induces Distinctive Proteomic Alterations in Olfactory Neuroepithelial Cells of Schizophrenia Patients

Abstract: A close epidemiological link has been reported between cannabis use and schizophrenia (SCZ). However, biochemical markers in living humans related to the impact of cannabis in this disease are still missing. Olfactory neuroepithelium (ON) cells express neural features and offer a unique advantage to study biomarkers of psychiatric diseases. The aim of our study was to find exclusively deregulated proteins in ON cells of SCZ patients with and without a history of cannabis use. Thus, we compared the proteomic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Based on this, we selected ZNF326 as a candidate biomarker. Previous studies had indicated that ZNF326 expression was associated with specific disease processes, such as in non-small cell lung cancer (NSCLC), triple-negative breast cancer (TNBC), glioma, and schizophrenia ( 30 - 34 ). Figure S5 shows the distribution in metastatic and non-metastatic patients, tumor and tumor-adjacent tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, we selected ZNF326 as a candidate biomarker. Previous studies had indicated that ZNF326 expression was associated with specific disease processes, such as in non-small cell lung cancer (NSCLC), triple-negative breast cancer (TNBC), glioma, and schizophrenia ( 30 - 34 ). Figure S5 shows the distribution in metastatic and non-metastatic patients, tumor and tumor-adjacent tissues.…”
Section: Resultsmentioning
confidence: 99%
“…A proteomic analysis performed on both neural progenitors and serum from cannabis users described an effect on the “immune system,” specifically proteins related to the interleukin-12 complex and enriched canonical pathways: “activation of liver X receptors/retinoid X receptor” (LXR/RXR), “farnesoid X receptors/retinoid X receptor activation” (FRX/RXR), “acute phase response signaling,” “atherosclerosis signaling and production of NO,” and “ROS in macrophages” ( Alasmari et al, 2021 ; Barrera-Conde et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amongst these, 102 DEPs were found exclusively in C/c compared to C/nc, and these proteins were predominantly associated with immune system function and RNA metabolism. Overall, their studies have established that cannabis affects the immune system and protein metabolism as the most common deregulated pathways between SCZ patients and cannabis users, as well as pathways pertaining to RNA metabolism, protein localization, and cellular signaling responses to external stimuli [70]. Taken together, these studies highlight the modulatory effects of cannabis on cellular function in the CNS, as well as its impact on the immune system and metabolism.…”
Section: Proteomic Studies On Cannabismentioning
confidence: 94%